Analysis of the Kinematic Accuracy Reliability of a 3-DOF Parallel Robot Manipulator. (26th February 2015) - Cui, Guohua; Zhang, Haiqiang; Zhang, Dan; Xu, Feng
Kinematic accuracy reliability is an important performance index in the evaluation of mechanism quality. By using a 3-DOF 3-P UU parallel robot manipulator as the research object, the position and orientation error model was derived by mapping the relation between the input and output of the mechanism. Three error sensitivity indexes that evaluate the kinematic accuracy of the parallel robot manipulator were obtained by adapting the singular value decomposition of the error translation matrix. Considering the influence of controllable and uncontrollable factors on the kinematic accuracy, the mathematical model of reliability based on random probability was employed. The measurement and calculation method for the evaluation of the mechanism's kinematic reliability level was also provided. By analysing the mechanism's errors and reliability, the law of surface error sensitivity for the location and structure parameters was obtained. The kinematic reliability of the parallel robot manipulator was statistically computed on the basis of the Monte Carlo simulation method. The reliability analysis of kinematic accuracy provides a theoretical basis for design optimization and error compensation.